Improving The Students’ Writing Ability In Descriptive Text Through Think-Talk-Write Strategy - Setiawati, Isye; Zuniati, Mai (Attractive : Innovative Education Journal, 2019)
This research is a Classroom Action Research (CAR). The subject of this research is tenth grade of MA Ma‘arif Roudlotut Tholibin Metro academic year 2018/2019 especially at class X Sains. It is consists of twenty three students. The data collecting techniques are test, observation, and questionnaire. The analysis of the data by using qualitative and quantitative data. The result showed that the students’ score in preliminary study, there was no one who passed the passing grade. Then, in the first cycle it is found that there were 12(52%) students who passed and the rest is 11(47%) students could not pass the passing grade. In cycle 2 there were an increase from cycle 1, that was 20(86%) students reached the passing grade and only 3(13%) who failed to accomplish the passing grade. The researcher concluded that TTW Strategy can improve students‘ writing ability in descriptive text. This showed of students‘ activities by observation, students‘ response by questionnaire, and students‘ score by test. The researcher found some dates that students interested, any progress when learned writing descriptive text by using Think-Talk-Write as strategy and the students felt better and improved for their writing ability in descriptive text. From observation students‘ active in the class. In cycle 2, 20(86%) students reached the passing grade and only 3(13%) who failed to accomplish the passing grade It indicated that think-talk-write strategy has considerable influence toward students’ writing ability in descriptive text and success Key words: Think-Talk-Write Strategy, Writing, Descriptive text